2017
DOI: 10.1007/s11676-017-0451-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution patterns of Symplocos congeners in a subtropical evergreen broad-leaf forest of southern China

Abstract: Studies on spatial distribution of congeneric species can supplement our understanding of species ecological processes. We analyzed population structure, spatial distribution, intra-and interspecific associations among six Symplocos tree species on a large (50 ha) plot in a subtropical, evergreen broad-leaf forest in southern China using spatial point pattern analysis methods. Our results suggested that the six Symplocos tree species were all clustered at small scales. The aggregation intensity of S. wikstroem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…To explore spatial relationships between SR and stumps, bivariate spatial pattern analyses were performed using g 12 (r): g 12 (r) = K 12 (r)/2πr. The interpretation of the parameters is similar to that of the univariate g(r), which was used in many studies of spatial pattern [19,26,29,58].…”
Section: Correlation and Spacing Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To explore spatial relationships between SR and stumps, bivariate spatial pattern analyses were performed using g 12 (r): g 12 (r) = K 12 (r)/2πr. The interpretation of the parameters is similar to that of the univariate g(r), which was used in many studies of spatial pattern [19,26,29,58].…”
Section: Correlation and Spacing Analysismentioning
confidence: 99%
“…Nevertheless, understanding the underlying biological process from the observed pattern remains a challenge [25,26] because the observed pattern has been modified by combinations of various past events over a long period and at various spatial scales, especially in forests [19,25]. Most tree species in forests worldwide are spatially aggregated at different scales and the spatial patterns of trees change with the developmental stage of the forest, particularly in natural forests not heavily disturbed by humans [23,[27][28][29]. Several studies have focused on the spatial patterns of trees according to forest development stage [30][31][32], some studies manifested that radial growth of trees and tree growth model was affected significantly by tree spatial position relative to skidding trails in conifer forest after different cutting methods [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Different growth rhythms of species may lead to interspecific repulsion (Comas et al 2009). Ledo et al (2011) reported that repulsion should be encountered between the young plants of two co-occurring species if they have dissimilar modes of seed dispersal, while Yang et al (2018) pointed out that repulsion may occur between species which have similar strategies for resource use. Moreover, Fig.…”
Section: Unmarked Analysismentioning
confidence: 99%
“…Most studies conducted SPPA in permanent plots (Wiegand et al 2007a;Bilek et al 2011;Zhao et al 2015) or constitute an opportunity for the creation of such plots (Velázquez et al 2014;Li et al 2017;Carrer et al 2018;Yang et al 2018;Zhang et al 2018). Permanent plots are typically large (generally 1 ha and can reach 50 ha) and have the advantage of being continuously monitored.…”
Section: Permanent Plot Scarcitymentioning
confidence: 99%
“…Many congeners coexist in most biodiverse tropical forest communities and low‐biodiversity temperate forest communities (Tanaka et al, 2008 ; Yamada et al, 2005 ; Zhang et al, 2010 ). However, some studies have found that the competition between congeneric species is not strong (Li et al, 2014 ; Sedio et al, 2012 ; Yang et al, 2018 ), and raising, the question could be how can similar congenerics coexist?…”
Section: Introductionmentioning
confidence: 99%